(untitled) (Revista INTEREDU11, 2021)
The objective of this article is to contribute to studies on women and science based upon an intersectionality between gender, race, generation and an anti-racist epistemology. From our places of activities (public and federal universities), we propose a dialogued Afro-descendant feminist autoethnography, bringing reflections beyond our experiences in facing racism and sexism. We reflect from the understanding that auto-ethnography is a qualitative research method that uses data about the self and the context in which it is inserted. Thus, the researcher is the center of the investigation bringing together, the subject and the object. In this sense, the self (researcher) and other selves (those outside) are brought together. In our exercise, we seek that this methodology brings two simultaneous voices that promote a statement –from individual or collective experiences– in the same text. We are two Afro-descendant women and doctors, from different generations (one in her thirties and another in her sixties), that when talking about multiple racisms in the educational area –although with a difference of three decades– our lives are still very alike, We point here, part of the networks of affection and religiosity that make up our crossings, our “ethos”, as well as our belongings and action to which they must be referred as support for the reports and anti-racist struggle, also within the scope of educational praxis.